Outcome after a liver resection of benign lesions. Issue 11 (3rd September 2015) - Hoffmann, Katrin; Unsinn, Michael; Hinz, Ulf; Weiss, Karl Heinz; Waldburger, Nina; Longerich, Thomas; Radeleff, Boris; Schirmacher, Peter; Büchler, Markus W.; Schemmer, Peter
Abstract Background Benign liver tumours represent a challenge in clinical management. There is considerable controversy with respect to the indications for surgery as the evidence for surgical treatment is variable. The aim of this retrospective study was to analyse the indication and outcome after resection of benign, solid liver lesions. Methods Data of 79 patients, who underwent liver resection between 2001 and 2012, were analysed for demographic and outcome parameters. Results Thirty‐eight patients with focal nodular hyperplasia (48%), 23 patients with haemangioma (29%) and 18 patients with hepatocellular adenoma (23%) underwent a hepatic resection. A major hepatic resection was performed in 23 patients (29%) and a minor resection in 56 patients (71%). The post‐operative mortality rate was zero and the 30‐day morbidity rate 13.9%. After a median follow‐up of 64 months, 75 patients (95%) were alive, and no patient had developed recurrent disease. Fifty‐four patients (68%) were pre‐operatively symptomatic, of which, 87% had complete or partial relief of symptoms after a liver resection. The incidence of symptoms increased with the lesions' size. Discussion The management of benign liver lesions necessitates an individualized therapy within a multidisciplinary, evidence‐based, treatment algorithm. Resection of benign liver lesions can be performed safely in well‐selected patients without mortality and low post‐operative morbidity.